2021
DOI: 10.1007/s00382-021-05798-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of Arctic gateways on sea ice and circulation in the Arctic and North Atlantic Oceans: a sensitivity study with an ocean-sea-ice model

Abstract: The impact of changes in volume, heat and freshwater fluxes through Arctic gateways on sea ice, circulation and fresh water and heat contents of the Arctic and North Atlantic Oceans is not fully understood. To explore the role played by each gateway, we use a regional sea-ice ocean general circulation model with a fixed atmospheric forcing. We run sensitivity simulations with combinations of Bering Strait (BS) and Canadian Arctic Archipelago (CAA) open and closed inspired by paleogeography of the Arctic. We sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 113 publications
0
7
0
Order By: Relevance
“…Changes in ocean inflow from the North Pacific and North Atlantic could also influence the upper ocean circulation in the Arctic Ocean (Spall, 2020;Karami et al, 2021;Wang et al, 2021b). For example, stronger Pacific Water inflow through the Bering Strait can increase the sea surface height along the continental slope of the Canada Basin so that the ocean circulation towards the Canadian Arctic Archipelago and Fram Strait is strengthened (Spall, 2020;Wang et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in ocean inflow from the North Pacific and North Atlantic could also influence the upper ocean circulation in the Arctic Ocean (Spall, 2020;Karami et al, 2021;Wang et al, 2021b). For example, stronger Pacific Water inflow through the Bering Strait can increase the sea surface height along the continental slope of the Canada Basin so that the ocean circulation towards the Canadian Arctic Archipelago and Fram Strait is strengthened (Spall, 2020;Wang et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, changes in the strength of stratification and halocline stability, which this study did not address, remain a large source of uncertainty due to substantial regional variability and model spread (e.g., Muilwijk et al, 2022;Pan et al, 2023;Shu et al, 2022). Several physical mechanisms can influence the exchange of heat fluxes between the ocean, atmosphere, and sea ice, including changes in wind forcing (Onarheim et al, 2015;Lien et al, 2017) and freshwater fluxes (Karami et al, 2021). For instance, there is evidence that wind-driven mixing will increase under icedepleted conditions (Perovich, 2011), which in turn will accelerate sea ice loss (Liang and Losch, 2018).…”
Section: Discussionmentioning
confidence: 90%
“…Consequently, a comparatively small reduction in salinity from freshwater input can weaken convective overturning, even in the case of surface cooling 34 ; by contrast, an increase in high-latitude salinity can have the opposite effect and strengthen convective overturning. However, as previous studies have shown [35][36][37] , both the AMOC strength and the North Atlantic climate are potentially sensitive to the status of the ocean gateways in the Arctic. At present, the North Pacific is less saline and has a relatively higher sea surface height than the Arctic Ocean.…”
Section: Importance Of Arctic Freshwater Transportmentioning
confidence: 94%